How are climate change and conflict disrupting children’s education across the Sahel? - Ramos, Cristina; Hounnou,Fèmi; Ouedraogo, Yacouba (2025)
This policy brief examines how the interaction between climate change and armed conflict disrupts children’s education across the Sahel, with a focus on Burkina Faso, Mali, Niger, and Chad. It shows that climate shocks such as droughts, floods, and extreme heat affect education systems that already face structural fragility, insecurity, and chronic underinvestment. Conflict, displacement, and targeted attacks on schools further compound these pressures, leading to widespread school closures, high dropout rates, and persistent learning poverty. Drawing on regional data and spatial analysis, the brief highlights how areas exposed to both climate stress and violence tend to record the lowest education outcomes. At the same time, it argues that education is not only a sector at risk but also a critical tool for long term resilience, climate adaptation, and peacebuilding. Using Burkina Faso as an in depth case study, the brief concludes with policy oriented recommendations to protect learning, strengthen climate resilient education systems, and integrate education more effectively into climate security responses across the Sahel.